Damasio's body-map-based view, Panksepp's affect-centric view, and the evolutionary advantages of consciousness. Issue 4 (2nd October 2019) - Anderson, Jane
Abstract : Although dualism has the advantage of being intuitively plausible, it is not compatible with a 21 st -century (scientific) world view. Jaak Panksepp and Antonio Damasio are contemporary writers who reject dualism, and whose views take the form of "biological naturalism". I first discuss how their views compare in five specific respects; and then I look more closely at how the different emphases of the views affect their ability to account for the evolutionary advantages of consciousness, specifically. Both authors agree that "consciousness" provides creatures with a survival advantage in terms of their ability to produce novel and/or flexible responses, their ability to plan ahead, and their motivation to promote their own survival – but the exact means by which they think these advantages are conferred, in each of these respects, differ. One might say that, whereas Damasio thinks the main evolutionary advantages of "consciousness" (the "higher reaches" of which are unique to humans) have to do with enabling creatures to work out what to do to promote their well-being, Panksepp thinks the main advantage of "consciousness" is that being "conscious" of affective feelings urgently motivates creatures to take action when their well-being is threatened. Considering that "working out what do" is only possible for a small selection of cognitively sophisticated organisms, I argue that Panksepp's account is more plausible than Damasio's account.